Konsep Lewi Dalam Estafet Kepemimpinan Gembala: Masihkah Relevan Bagi Gereja Saat Ini? - Ruslim, Samuel Kelvin; Ceria, Ceria; Nainggolan, Imayanti; Widjaja, Fransiskus Irwan; Tafonao, Talizaro (Sekolah Tinggi Teologi Kharisma, 2022)
This study was conducted to explore the concept of Levitical leadership in the Bible. The problem that often occurs is that even if there are leaders who are born genetically because they are inherited, strict rules are still needed so that the next generation of churches can continue the leadership relay well. Given the existence of a church that carries the concept of the Levitical priesthood, the writer is interested in examining whether it is still relevant to the church today and formulating it in a scientific study, namely